Effects of Ni/Co doping on structural and electronic properties of 122 and 112 families of Eu based iron pnictides - Joanna Stępień; Damian Rybicki; Marcin Sikora; Zbigniew Bukowski; Michał Babij; Łukasz Gondek; Czesław Kapusta; Tomasz Strączek; Kamil Goc; Danilo Oliveira De Souza (Scientific Reports, 2023)
Abstract Superconductivity in high-temperature superconductors such as cuprates or iron pnictides is typically achieved by hole or electron doping and it is of great interest to understand how doping affects their properties leading to superconductivity. To study it we conducted Fe and As K edge x-ray absorption spectroscopy measurements on several electron doped compounds from the 112 and 122 family of Eu-based iron pnictides. XANES and EXAFS results confirm that dopants are located at expected sites. For both families we found an electron charge redistribution between As and Fe occurring with doping. The changes it caused are stronger in the 112 family and they are bigger at As sites, which indicates that doped charges are predominantly localized on the dopant site. However, the results obtained do not provide clues why Ni doping in 122 family does not lead to occurrence of superconductivity.